2022
DOI: 10.1097/tp.0000000000004251
|View full text |Cite
|
Sign up to set email alerts
|

The Mycophenolate-based Immunosuppressive Regimen Is Associated With Increased Mortality in Kidney Transplant Patients With COVID-19

Abstract: Background. The chronic use of immunosuppressive drugs is a key risk factor of death because of coronavirus disease 2019 in kidney transplant recipients (KTRs), although no evident association between the class of immunosuppressive and outcomes has been observed. Thus, we aimed to compare COVID-19-associated outcomes among KTRs receiving 3 different immunosuppressive maintenance regimes. Methods. This study included data from 1833 KTRs with COVID-19 diagnosed between March 20 and April 21 extracted from the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…In the TANGO cohort, the withdrawal rates of tacrolimus and mycophenolate/everolimus were 23% and 65%, respectively [22]. Similarly, in a Brazilian multicenter study that was conducted before the vaccination era, it was observed that among KTRs diagnosed with COVID-19 and receiving an immunosuppressive regimen based on calcineurin inhibitors, patients treated with mycophenolate had a higher frequency of immunosuppression changes (61.6%, p < 0.001) than those treated with azathioprine (36.0%) or mTOR inhibitors (38.2%) [29]. Similar results were observed when immunosuppression was completely discontinued: mycophenolate (21.5%), azathioprine (19.3%), and mTOR inhibitors (12.9%, p = 0.02).…”
Section: Immunosuppression Management and Viral Treatmentmentioning
confidence: 88%
See 2 more Smart Citations
“…In the TANGO cohort, the withdrawal rates of tacrolimus and mycophenolate/everolimus were 23% and 65%, respectively [22]. Similarly, in a Brazilian multicenter study that was conducted before the vaccination era, it was observed that among KTRs diagnosed with COVID-19 and receiving an immunosuppressive regimen based on calcineurin inhibitors, patients treated with mycophenolate had a higher frequency of immunosuppression changes (61.6%, p < 0.001) than those treated with azathioprine (36.0%) or mTOR inhibitors (38.2%) [29]. Similar results were observed when immunosuppression was completely discontinued: mycophenolate (21.5%), azathioprine (19.3%), and mTOR inhibitors (12.9%, p = 0.02).…”
Section: Immunosuppression Management and Viral Treatmentmentioning
confidence: 88%
“…Similarly, the requirement for mechanical ventilation was higher for mycophenolate than for azathioprine (26.8% vs. 17.8%, p < 0.001); no difference was found for mTOR inhibitors. In a multivariate analysis, compared with azathioprine, the 90-day risk of death increased by 46% with mycophenolate and decreased by 41% with mTOR inhibitors [29].…”
Section: Outcomes and Predictorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Whether MPAassociated impairment of CMV cell-mediated immunity, as observed after severe acute respiratory syndrome coronavirus 2 infection, in which patients receiving MPA demonstrated a higher COVID-19 associated lethality and poor vaccine response, outweighs mTORi-associated preservation of CMV cell-mediated immunity remains to be determined. 19,20 The other uncertainty regarding viral infection after kidney transplantation is whether mTORi show similar pharmacodynamic properties to control BKVPyV replication as observed with CMV. 21 The data of this study suggest that the use of mTORi is not associated with a lower proportion of patients developing BKVPyV viremia nor with the magnitude of individual viral load measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Whether MPA-associated impairment of CMV cell–mediated immunity, as observed after severe acute respiratory syndrome coronavirus 2 infection, in which patients receiving MPA demonstrated a higher COVID-19 associated lethality and poor vaccine response, outweighs mTORi-associated preservation of CMV cell–mediated immunity remains to be determined. 19,20…”
Section: Discussionmentioning
confidence: 99%